A Simple and Fast Algorithm for Traffic Flow Control in High-Speed Computer Networks - Alfaro-Marchant, M (Institute of Electrical and Electronics Engineers Inc., 2018)
The development of an algorithm for the control of traffic flows that avoids situations of congestion is a hot topic in the computer networks. This paper presents a mathematical model for a general computer network and then discrete control theory is used as a key tool to design the traffic flow control algorithm that avoids congestion in a high-speed computer network, the proposed algorithm also ensures the stability of the computer network. The results of the simulations show that the proposed algorithm is able to adjust the sending speed and queue level in the buffer rapidly. In addition, the method is easy to implement to a high-speed computer network. © 2018 IEEE.